The Relative Effects of Manual Versus Automatic Exposure Control on Radiation Dose to Vital Organs in Total Hip Arthroplasty. Issue 1 (1st January 2018) - Harper, Katharine D.; Li, Shidong; Jennings, Rachel; Amer, Kamil M.; Haydel, Christopher; Ali, Sayed
Abstract : Introduction: Technologic advances have reduced medical radiation exposure while maintaining image quality. The purpose of this study was to determine the effects of the presence of total hip arthroplasty implants, compared with native hips, on radiation exposure of the most radiosensitive organs when manual and automatic exposure control settings are used. Methods: Detection probes were placed at six locations (stomach, sigmoid colon, right pelvic wall, left pelvic wall, pubic symphysis, and anterior pubic skin) in a cadaver. Radiographs were obtained with the use of manual and automatic exposure control protocols, with exposures recorded. A total hip arthroplasty implant was placed in the cadaver, probe positioning was confirmed, and the radiographs were repeated, with exposure values recorded. Results: The control probe placed at the stomach had values ranging from 0.00 mSv to 0.01 mSv in protocols with and without implants. With the manual protocol, exposures in the pelvis ranged from 0.36 mSv to 2.74 mSv in the native hip and from 0.33 mSv to 2.24 mSv after implant placement. The increases in exposure after implant placement, represented as relative risk, were as follows: stomach, 1.000; pubic symphysis, 0.818; left pelvic wall, 1.381; sigmoid colon, 1.550; right pelvic wall, 0.917; and anterior pubic skin, 1.015. With automatic exposure control, exposures in the pelvis ranged from 0.07 mSv to 0.89 mSv in the native hip and from 0.21 mSv to 1.15 mSv after implant placement. With automatic exposure control, the increases in exposure after implant placement, represented as relative risk, were as follows: stomach, 1.000; pubic symphysis, 1.292; left pelvic wall, 1.476; sigmoid colon, 2.182; right pelvic wall, 3.000; and anterior pubic skin, 1.378. Discussion: The amount of radiation to which patients are exposed as a result of medical procedures or imaging, and whether exposure is associated with an increased risk of malignant transformation, are the subject of ongoing debate. We found that after insertion of a total hip arthroplasty implant, exposure values increased threefold at some anatomic locations and surpassed 1 mSv, the generally accepted threshold for concern. Conclusion: Radiation exposure to radiosensitive organs increased up to threefold after total hip implantation with automatic exposure control and up to approximately 1.5 times with the manual protocol. Doses were greater with manual exposures than with automatic exposure control (except at the control probe on the stomach, where exposure was negligible, as expected). However, after implant placement, doses increased more with automatic exposure control than with manual exposure. This difference can be attributed to increased scatter and the difficulty of dose modification because of the density of the implant. Current radiographic protocols should be reassessed to determine if the benefits of frequent radiographs outweigh the newly demonstrated risks.